Ocular hypertension: a comparative follow-up of black and white patients. Issue 10 (October 1978) - David, R; Livingston, D; Luntz, M H
Abstract : Forty-four eyes in 25 black patients are compared with 92 eyes of 47 white patients in a population with ocular hypertension followed up for 1 to 12 years in a glaucoma clinic. The black patients present at a younger age than the whites and their mean initial intraocular pressure is significantly higher. The fact that more black ocular hypertensives developed glaucoma--8 eyes (18.1%) in the black population as compared with 5 eyes (5.4%) in the white population--is attributed to these two differences.